2015
DOI: 10.1111/imb.12187
|View full text |Cite
|
Sign up to set email alerts
|

The β‐N‐acetylhexosaminidase gene family in the brown planthopper, Nilaparvata lugens

Abstract: β-N-Acetylhexosaminidases (HEXs) are enzymes that can degrade the chitin oligosaccharides that are produced by the activity of chitinases on chitin in insects. Using bioinformatic methods based on genome and transcriptome databases, 11 β-N-acetylhexosaminidase genes (NlHexs) in Nilaparvata lugens were identified and characterized. Phylogenetic analysis revealed a six-grouped tree topology. The O-Linked N-acetylglucosaminidase (O-GlcNAcase) group includes NlHex11, which harbours a catalytic domain that differs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 31 publications
(46 reference statements)
6
40
0
Order By: Relevance
“…Investigation showed that, from 2000 to 2010–2011, rice pests caused a loss of up to 48 million ha in China (Zhao et al 2014). The hemimetabolous Brown planthopper Nilaparvata lugens Stål (Hemiptera: Delphacidae), which causes huge yield losses directly, is one of the most destructive insect pests, as they can only feed and breed on rice or wild rice (Xi et al 2014, 2015a,b). This pest damages rice plants by directly sucking the phloem sap and transmits plant viruses (Ghaffar et al 2011, Yang et al 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation showed that, from 2000 to 2010–2011, rice pests caused a loss of up to 48 million ha in China (Zhao et al 2014). The hemimetabolous Brown planthopper Nilaparvata lugens Stål (Hemiptera: Delphacidae), which causes huge yield losses directly, is one of the most destructive insect pests, as they can only feed and breed on rice or wild rice (Xi et al 2014, 2015a,b). This pest damages rice plants by directly sucking the phloem sap and transmits plant viruses (Ghaffar et al 2011, Yang et al 2014).…”
mentioning
confidence: 99%
“…Originally, insecticide control was an important and very convenient way to control and decrease pest populations, but its improper use has led to pest resurgence and resistance, and to the accumulation of chemical residues (Xi et al 2014). In N. lugens , gene-function studies have also shown that RNAi of target genes could be used a pest-control strategy (Wang et al 2012, 2015; Xi et al 2014, 2015a,b; Liu et al 2015; Zhao et al 2016; Yang et al 2017). …”
mentioning
confidence: 99%
“…Enolase gene (Eno1) silencing revealed down-regulation of mRNA level significantly in N. lugens and also decreased the egg laying capacity and population size during next generation of the planthopper [100]. Silencing of N-acetylhexosaminidase gene causes the molting and death of brown planthopper [108] Here we have mentioned some roles of viral suppressors for Rice grassy stunt virus.…”
Section: Planthoppersmentioning
confidence: 94%
“…In another study, silencing acyl-coenzyme A oxidase ( ACO ) [119,120] and glutamine synthetase ( GS ) [121] decreased the reproduction and population growth in BPH females, while knockdown of NIHsp90 by dsRNA injection reduced the survival and verified its role in thermotolerance [122]. Another study demonstrated the importance of β- N-acetylhexosaminidase gene family in BPH and the silencing of this gene caused molting failure and death [123]. Yang et al (2016) [124] demonstrated that knockdown of two trehalose-6-phosphate synthases ( TPS1 and TPS2 ) severely affected chitin metabolism and increased molting deformities and mortality rates, and showed that the nutritional signaling regulates Vitelogenin synthesis and egg development in N. lugens [125,126].…”
Section: Rnai-based Approaches For the Control Of Insect Vectorsmentioning
confidence: 99%